PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING (PT BANK RAKYAT INDONESIA PERSERO TBK CABANG BANJARMASIN SAMUDERA) - Nadia Mauliditta Septiana; Dwi Wahyu Artiningsih; Hairudinor Hairudinor (Universitas Lambung Mangkurat, 2021)
The purpose of this study is to analyze the Effect of Service Quality on Customer Loyalty with Customer Satisfaction (Case Study of PT Bank Rakyat Indonesia Persero Tbk Banjarmasin Samudera Branch. The type used in this research is explanatory research because this research explains the causal relationship between research variables through the hypothesis test that has been formulated previously. The analytical method uses Structural Equation Model (SEM) with Partial Least Square (PLS) Program. The results of this study prove that Service Quality has no effect on Customer Satisfaction at BRI Bank Prince Samudera Banjarmasin Branch, while Customer Satisfaction has a positive and significant effect on Customer Loyalty. And Service Quality has a positive and significant effect on Customer Loyalty.The results of this study prove that Service Quality has no effect on Customer Satisfaction at BRI Bank Prince Samudera Banjarmasin Branch, while Customer Satisfaction has a positive and significant effect on Customer Loyalty. And Service Quality has a positive and significant effect on Customer Loyalty.Keywords: Service Quality, Customer Loyalty, and Customer Satisfaction